Difference between revisions of "2003 USAMO Problems/Problem 5"
(→Solution) |
|||
Line 6: | Line 6: | ||
solution by paladin8: | solution by paladin8: | ||
− | WLOG, assume <math>a + b + c = 3</math>. | + | WLOG, assume <math>a + b + c = 3</math> since all terms are homogeneous. |
Then the LHS becomes <math>\sum \frac {(a + 3)^2}{2a^2 + (3 - a)^2} = \sum \frac {a^2 + 6a + 9}{3a^2 - 6a + 9} = \sum \left(\frac {1}{3} + \frac {8a + 6}{3a^2 - 6a + 9}\right)</math>. | Then the LHS becomes <math>\sum \frac {(a + 3)^2}{2a^2 + (3 - a)^2} = \sum \frac {a^2 + 6a + 9}{3a^2 - 6a + 9} = \sum \left(\frac {1}{3} + \frac {8a + 6}{3a^2 - 6a + 9}\right)</math>. | ||
Line 16: | Line 16: | ||
---- | ---- | ||
---- | ---- | ||
− | |||
− | |||
== Resources == | == Resources == |
Revision as of 09:57, 10 April 2012
Problem
Let ,
,
be positive real numbers. Prove that
![$\dfrac{(2a + b + c)^2}{2a^2 + (b + c)^2} + \dfrac{(2b + c + a)^2}{2b^2 + (c + a)^2} + \dfrac{(2c + a + b)^2}{2c^2 + (a + b)^2} \le 8.$](http://latex.artofproblemsolving.com/d/2/b/d2be8552ac3b2dcfb8d235a80ddc4d812b2f2155.png)
Solution
solution by paladin8:
WLOG, assume since all terms are homogeneous.
Then the LHS becomes .
Notice , so
.
So as desired.